2014
DOI: 10.3201/eid2002.130860
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus in Employees and Mice at Multipremises Feeder-Rodent Operation, United States, 2012

Abstract: Outbreaks can be prevented with strict biosecurity and microbiological monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 25 publications
1
36
0
1
Order By: Relevance
“…Although virus was never detected in healthy individuals and all patients with confirmed Wēnzhōu virus infections experienced similar symptoms of acute febrile bronchitis, the non-detection of co-infecting agents in three cases despite extensive testing does not mean that other untested or unknown pathogens were not present. However the clinical picture observed was similar to that reported for milder LCMV infection ( Baum et al, 1966 ; Knust et al, 2014 ). If like LCMV, Wēnzhōu virus rarely causes distinctive severe disease, then despite the high apparent incidence of the infection indicated by the retrospective serological study, causality is unlikely to be confirmed without further surveys.…”
Section: Discussionsupporting
confidence: 86%
“…Although virus was never detected in healthy individuals and all patients with confirmed Wēnzhōu virus infections experienced similar symptoms of acute febrile bronchitis, the non-detection of co-infecting agents in three cases despite extensive testing does not mean that other untested or unknown pathogens were not present. However the clinical picture observed was similar to that reported for milder LCMV infection ( Baum et al, 1966 ; Knust et al, 2014 ). If like LCMV, Wēnzhōu virus rarely causes distinctive severe disease, then despite the high apparent incidence of the infection indicated by the retrospective serological study, causality is unlikely to be confirmed without further surveys.…”
Section: Discussionsupporting
confidence: 86%
“…In the absence of barriers to superinfection, an incalculable number of novel viral genotype configurations, made even more numerous by frequent intra-segment recombination and an error-prone polymerase, could rapidly evolve and accumulate within individual animals and in breeding facilities. In theory, this situation could be exacerbated by the introduction of mammalian arenavirus-infected rodents as feedstock [66], although it is unknown whether recombinant or reassortant mammalian/reptile arenaviruses are possible or viable. Regardless, further investigation of high-density reptile breeding and feed rodent facilities should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The disease burden in humans is unknown; an estimated 5% of U.S. house mice carry LCMV (4). Human infection occurs by inhalation of aerosolized urine and droppings of infected rodents (5). The virus is a fetal teratogen, and transplacental vertical transmission with severe effects on infants has been described (6); infection after solid organ transplant (7-9) also have been reported.…”
mentioning
confidence: 99%